Cómo se vivencia el desempeño laboral frente al burnout en los docentes de una institución educativa en el distrito especial de Buenaventura (2023)
It is research that tries to analyze how job performance is experienced in the face of burnout in teachers of an educational institution in the city of Buenaventura. An in-depth investigation was carried out through the phenomenological paradigm; The study was carried out from a qualitative approach with a descriptive scope where initially the level of burnout in teachers was identified through the burnout Omint questionnaire, where different aspects such as emotional exhaustion, depersonalization and personal fulfillment were evaluated, and then characterize the experiences of teachers and the association that burnout has with job performance, which was carried out through an interview where the participants presented their perceptions and experiences of the existing problems in the workplace.